SEBUAH KASUS EKSPERIMEN: TINJAUAN FILOSOFIS - DR. JUMANTO Jumanto (Serat Acitya, 2020)
This article reports an experimental research viewed from a philosophical approach. As the philosophy suggests, its aspects i.e. ontology, epistemology, and axiology, play an important role in the application of how philosophy finds ways towards the development of a science, in this case, the applied linguistics on the teaching and learning process and its attributive aspects, i.e. students’ learning factors. Conclusions, implications, and suggestions are given upon the results of the research.